2022
DOI: 10.1136/bmjopen-2021-060367
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and antibody seroprevalence in routine surveillance patients, healthcare workers and general population in Kita region, Mali: an observational study 2020–2021

Abstract: ObjectiveTo estimate the degree of SARS-CoV-2 transmission among healthcare workers (HCWs) and general population in Kita region of Mali.DesignRoutine surveillance in 12 health facilities, HCWs serosurvey in five health facilities and community serosurvey in 16 villages in or near Kita town, Mali.SettingKita region, western Mali; local health centres around the central (regional) referral health centre.ParticipantsPatients in routine surveillance, HCWs in local health centres and community members of all ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The infection rate among healthcare workers suggests that SARS-CoV-2 may have been more widespread than reported in the Malian population. This was confirmed in a rural study that demonstrated up to 45% seropositivity in community members over the age of 60 in the same time period [39]. Viral strains such as the one reported here, which have the capacity for rapid reproductive rates, may have contributed to the wide dissemination of the SARS-CoV-2 virus in the population.…”
Section: Discussionsupporting
confidence: 82%
“…The infection rate among healthcare workers suggests that SARS-CoV-2 may have been more widespread than reported in the Malian population. This was confirmed in a rural study that demonstrated up to 45% seropositivity in community members over the age of 60 in the same time period [39]. Viral strains such as the one reported here, which have the capacity for rapid reproductive rates, may have contributed to the wide dissemination of the SARS-CoV-2 virus in the population.…”
Section: Discussionsupporting
confidence: 82%
“…The comparison between study-based estimates and WHO-reported estimates are as shown in Table 3 and Figure 5. For seven of the included prevalence studies 27,[48][49][50][51][52][53] (marked with * in Table 3), WHO reported daily cumulative COVID-19 cases were not available when stratified by age group, thus all-ages prevalence was used as a comparator. Out of the 28 studies, 4 studies from England 40,43,[45][46][47] , United…”
Section: General Description Of the Studiesmentioning
confidence: 99%
“…These serosurveys can give an estimation of the proportion of individuals that have been exposed to SARS‐CoV‐2, providing critical data to inform decision making on control strategies such as vaccination [ 5 ]. This approach has been extensively used for SARS‐CoV‐2 globally and especially in African countries [ 3 , 8 , 9 , 10 ] where testing capacity was an issue, under the coordination of the World Health Organization (WHO), in the UNITY protocol [ 11 ].…”
Section: Introductionmentioning
confidence: 99%